¿Qué es calidad en educación? Reflexión en torno al desafío de mejorar la educación (2020)
The term educational quality has been in constant evolution and transformations, both for educational systems and for institutions that apply the education process, for this reason it is important to be able to analyze the evolution process that the evaluation of educational quality has experienced. It is necessary to carry out an analysis in which the most relevant elements that can intervene in the process of educational quality are presented, hence the importance of this theoretical article that is based on how education is a process of transformation that really looks for educational quality, as Egido Galvez puts it, in his writing "reflections on the evaluation of educational quality", (GálVez, 2005) in which it is analyzed and reflected on what should be considered as educational quality and where it has emerged I finish, using the knowledge that can be had about the educational quality. For the article, a reflection on the term of educational quality is taken as a foundation, in the second measure as for the 21st century, a process of evolution with respect to education has been expected, from different perspectives, including the use of new models of teaching and learning for this reason, the article tries to analyze the elements that can improve the quality of education, for example through ICTs, as Pedro Ravela and others raise it to address the importance, purposes and uses of evaluations large-scale standardization of learning and school achievements that have been made in Latin America and the Caribbean, (Pedro Ravela et al., 2008), this work seeks to analyze the large-scale standardized evaluation to produce information that is known by its performance comparisons of students belonging to different cultural and regional contexts and, even, to different countries, which allows der the panorama of the continent through different tests and student censuses. And third, as modern states have tried to focus their efforts on education, designing different strategies, including the evaluation of competence, as defined by the author, one of the cornerstones of current educational policies, Calero and other (2012), to the point of referencing fundamental and reasonable elements understood as the social reaffirmation and the appropriation of the educational process, for this reason the attribution of the different systems and expectations is necessary. For this reason, it is important to analyze the different elements that are integrated into the different evaluations, especially the evaluation by competencies, which highlights and establishes government policies, by claiming that the only element that may be feasible to measure educational quality are external tests.